2015
DOI: 10.1111/cen.12773
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone deficiency after childhood bone marrow transplantation with total body irradiation: interaction with adiposity and age

Abstract: GHD was more prevalent in BMT/TBI survivors than expected for the CRT dose in TBI, worsened with time and persisted into adulthood. GHD could not be explained by adiposity. There was no evidence of GH neurosecretory dysfunction or resistance after BMT/TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…[2][3][4][5][6][7][8] The causes of impaired physical performance include deficits in cardiopulmonary and musculoskeletal function, which may be related to both the primary treatment and the conditioning regimen before HCT. 3,[8][9][10][11][12][13][14][15] Also, growth hormone (GH) deficiency may develop after HCT 16,17 and may impair muscle strength and physical performance. 18 Impaired physical performance may also be caused by, as well as predispose to, physical inactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The causes of impaired physical performance include deficits in cardiopulmonary and musculoskeletal function, which may be related to both the primary treatment and the conditioning regimen before HCT. 3,[8][9][10][11][12][13][14][15] Also, growth hormone (GH) deficiency may develop after HCT 16,17 and may impair muscle strength and physical performance. 18 Impaired physical performance may also be caused by, as well as predispose to, physical inactivity.…”
Section: Introductionmentioning
confidence: 99%
“…A final total of 20 papers were included-seven controlled studies [1,10,[18][19][20][21][22], five uncontrolled studies [23][24][25][26][27] and eight case reports/series [28][29][30][31][32][33][34][35]. Only one study included an intervention [23].…”
Section: Search Resultsmentioning
confidence: 99%
“…Wei et al also found significantly lower BMI and fat mass index, but this was compared to obese controls [10,22]. Three studies found significantly higher body fat: body fat % compared to short stature controls [19] and healthy controls [20] and whole body fat mass z score compared to reference controls [1]. Data from Adachi et al [26] suggests BMI may be lower than leukaemic controls with no TBI, and, although significance could not be tested, within the normal range for age.…”
Section: Total Body Fatmentioning
confidence: 94%
See 1 more Smart Citation
“…Patient's age was not part of the exclusion criteria as both adult and pediatric patients were included in our analysis. Studies that did not assess the direct association of DM/IGM with TBI or did not have eligible study population were excluded (Chemaitilly et al, 2009;Majhail et al, 2009;Baker et al, 2010;Frisk et al, 2011;Sohn et al, 2011;Bizzarri et al, 2015;Davis et al, 2015;Wei et al, 2015;Wilhelmsson et al, 2015;Wei et al, 2016;Bielorai et al, 2017;Friedman et al, 2017).…”
Section: Methodsmentioning
confidence: 99%